2002
DOI: 10.1300/j082v42n04_08
|View full text |Cite
|
Sign up to set email alerts
|

The Personality Variable Openness to Experience as It Relates to Homophobia

Abstract: The present study investigated personality and demographic variables of homophobic and non-homophobic individuals. Variables explored included the personality characteristics Neuroticism, Extroversion, and Openness to Experience. The following demographic variables were also explored: gender role beliefs, gender, and personal contact. Participants included 123 students from a large Western university, enrolled in introductory courses in psychology or sociology. Participants completed a questionnaire packet con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
52
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 38 publications
12
52
2
4
Order By: Relevance
“…The view of homosexuality as something undesirable, immoral and sinful may well be more frequent in people with religious beliefs (Toro-Alfonso & Varas-Díaz, 2007). Our results also support previous research that has shown greater homophobia to be associated with a lack of contact with gay men and lesbian women (e.g., Berkman & Zinberg, 1997;Cullen et al, 2002;Sakalli, 2002;Shidlo, 1994). Proximity to, and interaction with, gay men and lesbian women might enable individuals to compare the stereotyped views of homosexuality, thus lowering this prejudice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The view of homosexuality as something undesirable, immoral and sinful may well be more frequent in people with religious beliefs (Toro-Alfonso & Varas-Díaz, 2007). Our results also support previous research that has shown greater homophobia to be associated with a lack of contact with gay men and lesbian women (e.g., Berkman & Zinberg, 1997;Cullen et al, 2002;Sakalli, 2002;Shidlo, 1994). Proximity to, and interaction with, gay men and lesbian women might enable individuals to compare the stereotyped views of homosexuality, thus lowering this prejudice.…”
Section: Discussionsupporting
confidence: 91%
“…Proulx, 1997), the majority show men to be more homophobic than women (Donnelly et al, 1997;Johnson et al, 1997;Jones et al, 2002;Lieblich & Friedman, 1985;Lingiardi et al, 2005;Maney & Cain, 1997;Sakalli, 2002;Steffens, 2005). There is also consensus among various studies that having contact with homosexual people is predictive of fewer homophobic attitudes or, to put it another way, a lack of contact with lesbian women and gay men is correlated with negative attitudes (Berkman & Zinberg, 1997;Cullen et al, 2002;Sakalli, 2002;Shidlo, 1994;Span & Vidal, 2003;Toro-Alfonso & Varas-Díaz, 2004;Waterman et al, 2001). As Farr (2000) points out, it would seem that the most powerful stimulus of homophobia is the belief that "I don't know any homosexuals".…”
mentioning
confidence: 99%
“…Consistent with previous research, men scored significantly higher than women on both homophobia [66,67] and transphobia levels [68]. One interpretation of these findings could be that more negative attitudes toward lesbian women, gay men, and transgender persons are not directly related to homosexuality and transgenderism per se, but to a more general adherence in men to traditional gender roles [12,13].…”
Section: Discussionsupporting
confidence: 86%
“…This evidence is coincided other information which has been obtained from the literature (Kite & Whitley, 1996;1998;Sakallı & Uğurlu, 2001;Cullen, Wright & Alessandri, 2002;Güney & et al, 2004;Çırakoğlu, 2006;Gormley & Lopez, 2010;Costa & Davies, 2012).…”
Section: Discussionsupporting
confidence: 92%